Can city planning instruments measure up to urban resilience indicator norms? A multi-criteria analysis of IUDF nominated sites in the Western Cape of South Africa - Christians, Edroy Garth (Stellenbosch : Stellenbosch University, 2022)
Thesis (MPhil)--Stellenbosch University, 2022.